Transcriptome-Wide Characterization of Alkaloids and Chlorophyll Biosynthesis in Lotus Plumule - Sun, Heng; Song, Heyun; Deng, Xianbao; Liu, Juan; Yang, Dong; Zhang, Minghua; Wang, Yuxin; Xin, Jia; Chen, Lin; Liu, Yanling; Yang, Mei (Frontiers in Plant Science, 2022)
Lotus plumule is a green tissue in the middle of seeds which predominantly accumulate bisbenzylisoquinoline alkaloids (bis-BIAs) and chlorophyll (Chl). However, the biosynthetic mechanisms of these two metabolites remain largely unknown in lotus. This study used physiological and RNA sequencing (RNA-Seq) approaches to characterize the development and molecular mechanisms of bis-BIAs and Chl biosynthesis in lotus plumule. Physiological analysis revealed that exponential plumule growth occurred between 9-15 days after pollination (DAP), which coincided with the onset of bis-BIAs biosynthesis and its subsequent rapid accumulation. Transcriptome analysis of lotus plumule identified a total of 8,725 differentially expressed genes (DEGs), representing ~ 27.7% of all transcripts in the lotus genome. Sixteen structural DEGs potentially associated with bis-BIAs biosynthesis were identified. Of these, 12 encoded O-methyltransferases (OMTs) which are likely involved in the methylation and bis-BIAs diversity in lotus. In addition, functionally divergent paralogous and redundant homologous gene members of BIAs biosynthesis pathway as well as transcription factors co-expressed with bis-BIAs and Chl biosynthesis genes were identified. Twenty-two genes encoding 16 conserved enzymes of the Chl biosynthesis pathway were identified, with majority being significantly up-regulated by Chl biosynthesis. Photosynthesis and Chl biosynthesis pathways were simultaneously activated during lotus plumule development. Moreover, our results showed that light-driven Pchlide reduction is essential for Chl biosynthesis in lotus plumule. These results will be useful for enhancing our understanding of alkaloids and Chl biosynthesis in plants.